R120G alphaB-crystallin promotes the unfolding of reduced alpha-lactalbumin and is inherently unstable. - Treweek, T; Rekas, A; Lindner, R; Walker, M; Aquilina, J; Robinson, C; Horwitz, J; Perng, MD; Quinlan, R; Carver, J (2005)
alpha-Crystallin is the principal lens protein which, in addition to its structural role, also acts as a molecular chaperone, to prevent aggregation and precipitation of other lens proteins. One of its two subunits, alphaB-crystallin, is also expressed in many nonlenticular tissues, and a natural missense mutation, R120G, has been associated with cataract and desmin-related myopathy, a disorder of skeletal muscles [Vicart P, Caron A, Guicheney P, Li Z, Prevost MC, Faure A, Chateau D, Chapon F, Tome F, Dupret JM, Paulin D and Fardeau M (1998) Nat Genet20, 92-95]. In the present study, real-time 1H-NMR spectroscopy showed that the ability of R120G alphaB-crystallin to stabilize the partially folded, molten globule state of alpha-lactalbumin was significantly reduced in comparison with wild-type alphaB-crystallin. The mutant showed enhanced interaction with, and promoted unfolding of, reduced alpha-lactalbumin, but showed limited chaperone activity for other target proteins. Using NMR spectroscopy, gel electrophoresis, and MS, we observed that, unlike the wild-type protein, R120G alphaB-crystallin is intrinsically unstable in solution, with unfolding of the protein over time leading to aggregation and progressive truncation from the C-terminus. Light scattering, MS, and size-exclusion chromatography data indicated that R120G alphaB-crystallin exists as a larger oligomer than wild-type alphaB-crystallin, and its size increases with time. It is likely that removal of the positive charge from R120 of alphaB-crystallin causes partial unfolding, increased exposure of hydrophobic regions, and enhances its susceptibility to proteolysis, thus reducing its solubility and promoting its aggregation and complexation with other proteins. These characteristics may explain the involvement of R120G alphaB-crystallin with human disease states.